Hubungan Antara Penguasaan Kosakata dengan Keterampilan Menulis Puisi Bahasa Jerman - Nur, Mursalim; Burhanuddin, Burhanuddin; Mannahali, Misnah (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to obtain data on the relationship between vocabulary mastery and German writing skills of class XI students of MAN 1 Makassar City. The sample in this study were students of class XI MIA 5 MAN 1 Makassar City which consisted of 1 class totaling 30 students. The sampling technique used was random sampling. The data were collected through a vocabulary mastery test and a poetry writing skill test. The research data were analyzed using the Product Moment correlation analysis technique. The results of this study indicate that there is no significant relationship between vocabulary mastery and writing skills in German, this is indicated by the value of rh (0.108) â‰¤ rt (0.361), with N = 30 at the 0.05% significance level.